Wide skin markings pattern: melanoma descriptor or patient‐related factor?. (1st May 2018) - Rishpon, A.; Marchetti, M.; Marghoob, A.
Abstract: Linked Article: Bassoli et al. Br J Dermatol 2018; 178 :e217–e218.